THE IMPACT OF IMPLEMENTING EDUCATIONAL SKILL TRANSFER STRATEGIES ON ENHANCING PROFESSIONAL COMPETENCIES IN INFORMATION AND COMMUNICATION TECHNOLOGY AMONG ALGERIAN UNIVERSITY STUDENTS (Lex localis - Journal of Local Self-Government, 2025)
This study aimed to measure the impact of implementing educational skill transfer strategies on the development of professional skills in the field of Information and Communication Technology (ICT) among Algerian university students. The research problem stems from the widening gap between academic outputs and the requirements of the digital labor market, which increasingly demands practical and applied competencies. To achieve the intended objectives, the study employed a descriptive-analytical approach. Data were collected from a sample of 324 students from various technical and engineering specializations using an online questionnaire, and analyzed through the Statistical Package for the Social Sciences (SPSS). The findings revealed a contradiction between the students’ strong theoretical background and their weak actual practical application. Moreover, the results confirmed a strong positive and statistically significant correlation between the two variables, with a Spearman correlation coefficient of 0.702. These results indicate that educational skill transfer strategies such as project-based learning and partnerships with the industrial sector are an essential necessity for preparing graduates. The study recommends intensifying efforts to integrate applied curricula and strengthen collaboration between universities and the business sector to bridge this critical gap.